Компактна мікросмужкова антена для частоти 915 мгц - Пономаренко, Є. Д. (ХНУРЕ, 2024)
The goal of the work is to develop a compact microstrip antenna for radio systems operating at frequencies of 915 MHz.
Keywords: компактна мікросмужкова антена; compact microstrip antenna